Դեղերի պատշաճ արտադրական գործունեության համակարգի ներդրման արդյունքների գնահատումը Հայաստանի Հանրապետությունում - Շաքարյան, Մ. Կ.; Սահակյան, Ա. Ե. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Исследования, проведенные среди производителей лекарственных средств в Республике Армения, показали, что система оценивания государством деятельности производителей в стране, в целом, привела к положительным результатам. Были получены результаты опроса производителей, деятельность которых соответствует требованиям надлежащей производственной практики, установленной в Республике Армения. Опросник был разработан с учетом задач, поставленных Правительством Республики Армения в рамках осуществления стратегического плана по экспорту лекарств, также с учетом обзора литературы. Studies conducted among manufacturers of medicinal products in the Republic of Armenia has shown that the implementation of assessment system from the Government side lead to positive results. It has been assumed the results of survey conducted of manufacturers complying with the Good Manufacturing Practice rules established in the Republic of Armenia. Questionnaire used in survey has been elaborated taking into account objectives assigned by the Government of the Republic of Armenia within the implementation of the strategic plan to enhance export of medicinal products and based on literature review.
Keywords: Therapeutics; Pharmacology